MycoMix and risk assessment: a contribute to improve risk analysis - Alvito, Paula (2015)
Risk analysis, is a powerful tool for including science-based knowledge in a systematic approach to food safety problems. The use of risk analysis can promote ongoing improvements in public health and provide a basis for expanding international trade in foods. Within risk analysis, the risk assessment results are quantitative or qualitative expressions of the likelihood of harmful effects associated with exposure to a chemical (WHO, 2010). Human risk assessment of combined exposure to multiple chemicals (chemical mixtures) poses several challenges to scientists, risk assessors and risk managers, namely the complexity of the terminology and problem formulation, the diversity of chemical entities, and the toxicological profiles and exposure patterns in test species and humans (EFSA, 2013). Mycotoxins are natural contaminants produced by fungi and its frequent co-occurrence in food poses a threat to human health, mainly to vulnerable population groups as children. MycoMix is an ongoing national project (2013-15) that explores the toxic effects of mixtures of mycotoxins in infant food and its potential health impact. This project aims to study the occurrence of multiple mycotoxins and toxicity interactions in infant foods and cereals consumed by Portuguese children and try to answer several questions: 1) Are children exposed daily to mycotoxins through food? 2) What are the quality and quantity that characterize this exposure? 3) Can this exposure bring harm to children? Answering these questions will raise novel approaches to: 1) apply new techniques on mycotoxin multiple detection, 2) understand the toxicity responses upon multiple mycotoxin exposures, and 3) implement new methodologies to characterize hazard and risk for children exposure to mycotoxins. A multidisciplinary team has been developing, for the first time in Portugal, i) a liquid chromatography (LC) method coupled with tandem mass-spectrometry (LC-MS/MS) for multimycotoxin detection in infant food developed and applied to study infant food consumed by Portuguese children, ii) cito and genotoxic assays to assess the toxicity of binary mixtures of mycotoxins detected in analyzed infant foods associated with the MIXTOX tool to assess the interactive effects, iii) in vitro methodologies to simulate the digestive and intestinal absorption processes of binary mixtures of mycotoxins, iv) a web-based dietary assessment and diet planning platform, the “OPEN Portugal”, to record infant food consumption data allowing simultaneously the assessment of the nutritional profile of the inquired children, and v) a set of deterministic, probabilistic (@RISK) and cumulative risk assessment approaches that allow the exposure assessment and risk characterization of Portuguese children to multiple mycotoxins in food. An overview of the results obtained within the MycoMix project will be presented, showing the patterns of the exposure of Portuguese infant to multiple mycotoxins as well as the scientific evidence of the toxic effects of mycotoxin mixtures using in vitro models. Hence,MycoMix outputs contribute for hazard identification and characterization as well as to exposure characterization, contributing for risk analysis.